An integrated modeling perspective on climate change mitigation and co-benefits in the transport sector - Jarusch Muessel; Robert Pietzcker; Johanna Hoppe; Philipp Verpoort; David Klein; Gunnar Luderer (Environmental Research Letters, 2025)
Transport research has long focused on comparing climate change mitigation strategies. However, it remains unclear how the effects of different strategies on climate and non-climate externalities compare. This paper assesses the mitigation potential of a comprehensive set of transport transformation strategies from an integrated modeling perspective. In doing so, it goes beyond the assessment of climate change by including health-related externalities. We analyze transformation scenarios clustered along three interventions: lifestyle changes (LSCs), electrification, and efficiency improvements. All clusters yield significant climate mitigation potential, with electrification most effectively reducing CO2 emissions. LSCs allow for immediate emission reductions, are effective in hard-to-electrify transport modes, and facilitate the overall energy system transformation. They also have the strongest impact on overall transport externalities, especially due to activity-related health benefits. When compared on a monetarized basis to the REF in 2050, for the EU, LSCs lead to a total benefit of 70 bn EUR/yr by reducing adverse externalities of motorized transport by 30% and increasing positive externalities of active mobility by 50%. Based on this, we conclude that policymaking should both advance the electrification of road transport and promote mobility behavior towards shared and active modes to minimize CO2 emissions while maximizing co-benefits.